Tờ trình tóm tắt dự án Luật sửa đổi, bổ sung một số điều của Luật Sở hữu trí tuệ (Số: 359 /TTr-CP) - Chính phủ (2021)
Toàn văn Tờ trình tóm tắt dự án Luật sửa đổi, bổ sung một số điều của Luật Sở hữu trí tuệ (Số: 359 /TTr-CP)